Five-phase induction motor drive-A comprehensive review - Kulandaivel, Gobikannan; Sundaram, Elango; Gunasekaran, Manavaalan; Chenniappan, Sharmeela (Frontiers in Energy Research, 2023)
Modern Electrical Vehicles (EV) and Electric Traction rely heavily on electrical drives. Every day, electric vehicles are being improved and expanded to include commercial vehicles such as passenger vehicles, goods delivery vehicles, and agricultural vehicles. Today, researchers are concentrating on multi-phase electrical drives to improve EV technology. This article provides a comprehensive analysis of the Five-Phase Induction Motor (FPIM) drive. The proposed study investigates the FPIM drive in terms of mathematical modeling and design, the different topologies of a Five-Phase Voltage Source Inverter (FPVSI) (Two-Level, Multi-Level, Matrix), the methodologies utilised to generate the pulse for FPVSI (Carrier-Based Pulse Width Modulation (CBPWM), Space Vector Pulse Width Modulation (SVPWM)), and the control of FPIM. This study evaluates the many strategies available in the literature for controlling the FPIM in order to assist researchers and industrial Research and Development (R&D) engineers in selecting the most suitable tool for their applications.